Radical Addition Enables 1, 2‐Aryl Migration from a Vinyl‐Substituted All‐Carbon Quaternary Center. (29th October 2020) - Li, Zexian; Wang, Minyan; Shi, Zhuangzhi
Abstract: An efficient method for photocatalytic perfluoroalkylation of vinyl‐substituted all‐carbon quaternary centers involving 1, 2‐aryl migration has been developed. The rearrangement reactions use fac ‐Ir(ppy)3, visible light and commercially available fluoroalkyl halides and can generate valuable multisubstituted perfluoroalkylated compounds in a single step that would be challenging to prepare by other methods. Mechanistically, the photoinduced alkyl radical addition to an alkene leads to the migration of a vicinal aryl substituent from its adjacent all‐carbon quaternary center with the concomitant generation of a C‐radical bearing two electron‐withdrawing groups that is further reduced by a hydrogen donor to complete the domino sequence. Abstract : A photocatalytic system was developed for perfluoroalkylation of vinyl‐substituted all‐carbon quaternary centers by using perfluoroalkyl halides with concomitant 1, 2‐aryl migration. This strategy possesses good functional‐group compatibility and can serve as a powerful synthetic tool for the construction of valuable perfluoroalkylated compounds that would be difficult to prepare by other methods.